Whose Smartphone Is It? Should two private companies have complete control over the world's cellphones? - Larus, James R. (Communications of the ACM, 2021)
The author discusses his thoughts about the dominance of high technology firms Apple and Google in the smartphone industry, particularly the control that the companies have over smartphone operating software. He examines the introduction of the Exposure Notification contact tracing framework during the COVID-19 pandemic and the control exercised by Apple and Google, the importance of application programming interfaces (APIs), and issues of privacy and privacy protocols.